A possible role for river restoration enhancing biodiversity through interaction with wildfire. Issue 10 (14th June 2022) - Pugh, Brittany E.; Colley, Megan; Dugdale, Stephen J.; Edwards, Patrick; Flitcroft, Rebecca; Holz, Andrés; Johnson, Matthew; Mariani, Michela; Means‐Brous, Mickey; Meyer, Kate; Moffett, Kevan B.; Renan, Lisa; et al.
Abstract: Background: Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The "pyrodiversity begets biodiversity" hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase: Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions: We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn ("Holiday Farm" wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a "triple win" of flood reduction, wildfire alleviation and biodiversity promotion.